Waxman's algorithm for non-Hermitian Hamiltonian operators. (21st February 2018) - Chamberlain, S R; Tucker, J G; Conroy, J M; Miller, H G
Abstract: An algorithm for finding the bound-state eigenvalues and eigenfunctions of a Hermitian Hamiltonian operator using Green's method, developed by Waxman [1 ], has been extended to include non-Hermitian Hamiltonian operators.